Intervenção psicomotora no processo de aprendizagem da escrita: um estudo de caso - Bugs, Paula Guimarães (2025)
Understanding human development and the factors that influence learning is fundamental for teaching practice, as this will contribute to a more effective intervention, making learning more meaningful. This research focuses on analyzing the relationship between the body and writing, specifically the relationship between lateral dominance, laterality, spatial orientation and difficulties in writing orientation. Before learning to write, it is necessary to engage in psychomotor work that promotes the development of spontaneous, coordinated, and rhythmic motor skills, which will help reduce issues related to dysgraphia or writing orientation. Objective: The aim of this study is to analyze and understand the influence of laterality on the learning process of writing orientation. Methodology: The research proposes a qualitative approach through a case study involving a participant who is 6 years and 6 months old and exhibits a peculiarity in writing orientation, writing words both from right to left and from left to right; however, she demonstrates neurological development within the expected standards for her age. The evaluative instruments aim to analyze the lateral dominance of the hand, eye, and foot. After the pre-test, a psychomotor intervention was conducted, consisting of ten sessions of 45 minutes each, held weekly. The intervention proposal included psychomotor activities related to the development of laterality, visuomotor coordination, and spatial orientation. At the end of the ten sessions, a post-test was conducted to verify whether there was any change in lateral dominance. Conclusion: it is possible to state that both the crossed laterality presented by the participant in one of the tests that assessed her lateral dominance or her undefined laterality, resulting from the other test performed, are strong elements to justify the difficulty presented by the participant in the process of appropriating the writing orientation.